The Dialect of Moush by the Evaluation of Researchers - MKRTCHYAN, GARIK (Bulletin of Yerevan University B: Philology, 2021)
In the present article, the brief history of the dialect of Moush is presented. The studies of the author have shown that structural peculiarities of the dialect of Moush were mainly studied by Qerovbe Patkanyan, Levon Mseryants, Hrachya Acharyan, Siranush H. Baghdasaryan-Tapaltsyan, Smbat Shahnazaryan, Qerob Madatyan, Bense, Karo Sasuni, Sargis and Misak Bdeans, Gevorg Jahukyan. The author comes to the conclusion that the study of the dialect of Moush has begun since the end of the 19th century and that process is still going on. According to G. Jahukyan’s multi-featured statistical classification of Armenian dialects the dialect of Moush is located in the Moush-Tigranakert or south-central dialectical group of the western area of Armenian dialects. It includes sub-dialects of Baghesh, Khlat, Artske, Artchesh, Manazkert, Moush, Bulanekh, Khnous, Alashkert.
Keywords: language, dialect, dialect of Moush, structural, Moush-Tigranakert, Qerovbe Patkanyan, Levon Mseryants, Bense, Baghesh, Khlat